Koncepcja „Beyond Budgeting” – perspektywy wykorzystania do zarządzania przedsiębiorstwami branży spożywczej - Soliwoda, Michał (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2011)
In the article the usefulness of the concept “Beyond Budgeting” in decisionmaking process as for business management was presented. The possibilities of using of this concept by food industry enterprises was assessed. In today’s economic environment the traditional budgetary does not meet the expectations of managers. “Beyond Budgeting” involves radical changes in the management system, including a fl exible organization. The possibilities of using new concept in the food industry enterprises are limited due to the traditional understanding of the budget in the organizational culture. In the future large food industry companies may abandon the traditional budgeting, but the process of implementing “Beyond Budgeting” will be evolutionary and will take several steps (among others “zero-based” budgeting, rolling budgeting).